Arbitrase Internasional dalam Penyelesaian Sengketa Penanaman Modal Asing: Tinjauan Praktis di Indonesia - Aprilia, Fanny (Jurnal Hukum & Pembangunan, 2024)
Indonesia has demonstrated a strong commitment to international arbitration by participating in various international conventions, such as the 1958 New York Convention, and by implementing supportive domestic legislation, such as Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. International arbitration offers advantages such as neutrality, specialized expertise, and legal certainty, making it a preferred mechanism for resolving foreign investment disputes. However, the implementation of arbitration in Indonesia still faces several challenges, including a lack of understanding of arbitration procedures among court officials and concerns about potential domestic court interference in the arbitration process. This paper highlights the importance of enhancing the capacity and understanding of court officials regarding arbitration and the need for policies that ensure the independence of the arbitration process. By addressing these challenges, Indonesia can strengthen its mechanisms for resolving investment disputes and enhance its attractiveness as a foreign investment destination.